2007
DOI: 10.1515/znc-2007-9-1007
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Triterpene Acids and Semi-Synthetic Derivatives against Oral Pathogens

Abstract: Triterpene acids (ursolic, oleanoic, gypsogenic, and sumaresinolic acids) isolated from Miconia species, along with a mixture of ursolic and oleanolic acids and a mixture of maslinic and 2-α-hydroxyursolic acids, as well as ursolic acid derivatives were evaluated against the following microorganisms: Streptococcus mutans, Streptococcus mitis, Streptococcus sanguinis, Streptococcus salivarius, Streptococcus sobrinus, and Enterococcus faecalis, which are potentially responsible for the formation of dental caries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 25 publications
2
45
0
4
Order By: Relevance
“…Maslinic acid (MA), a pentacyclic triterpene acid, is widely present in dietary plants, especially abundant in olive fruit skins and hawthorn. The compound has attracted much interest owing to its proven pharmacologic safety and its many biologic activities, such as anti-inflammatory, (2) antiviral, (3) antioxidant, (2,4) and antidiabetogenic activities (5,6) and anti-colon cancer (7) and antiastrocytoma (8) properties. In this study we examined the effects of MA on osteoclast differentiation and function in vitro and in vivo and then elucidated the underlying molecular mechanisms.…”
mentioning
confidence: 99%
“…Maslinic acid (MA), a pentacyclic triterpene acid, is widely present in dietary plants, especially abundant in olive fruit skins and hawthorn. The compound has attracted much interest owing to its proven pharmacologic safety and its many biologic activities, such as anti-inflammatory, (2) antiviral, (3) antioxidant, (2,4) and antidiabetogenic activities (5,6) and anti-colon cancer (7) and antiastrocytoma (8) properties. In this study we examined the effects of MA on osteoclast differentiation and function in vitro and in vivo and then elucidated the underlying molecular mechanisms.…”
mentioning
confidence: 99%
“…As previously identified (Wojnicz et al, 2012), MIC values were high and ranged from 512 µg/mL to >1024 µg/mL. Cunha et al (2007) Garo et al (2007) noted that the MIC of AA against P. aeruginosa was 128 µg/mL. Djoukeng et al (2005) showed that the MICs of AA fractions obtained from the extract of Syzygium guineense were much higher for gram-negative Shigella sonnei and E. coli strains in comparison with gram-positive B. subtilis.…”
Section: Antibacterial Activitymentioning
confidence: 67%
“…In our study we used AA, the therapeutic activity of which is poorly described, and UA, the antimicrobial action of which, mainly against gram-positive bacteria, has been described in several reports (Chandramu et al, 2003;Cunha et al, 2007;Fontanay et al, 2008;Kurek et al, 2010). Table 2 summarizes the in vitro susceptibilities of the 20 isolates of E. coli to AA and UA.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…al., 1987;Arisawa et al, 1993;Xu et al, 2009). By means of spectroscopic data and literature (Seebacher et al, 2003;Silva et al, 2008), it was possible to confirm the identity of the 5 as ursolic acid, (3β-hydroxy-urs-12-en-28-oic acid), an ursanic triterpene isolated from several species (Fu et al, 2005;Leite et al, 2006;Cunha et al, 2007).…”
Section: Cytotoxicity Assays With Human Cancer Cell Lineagesmentioning
confidence: 91%